Brain connectivity and metacognition in persons with subjective cognitive decline (COSCODE): Retrospective analyses on the Geneva Memory Clinic cohort: Neuroimaging / differential diagnosis. (7th December 2020) - Ribaldi, Federica; Altomare, Daniele; Garibotto, Valentina; Mendes, Aline; Assal, Frederic; Eshmawey, Mohamed; Chicherio, Christian; Frisoni, Giovanni B
Abstract: Background: Advances in the Alzheimer's disease (AD) field have enhanced awareness on brain health and prevention. This brings an increasing number of adults to ask for help in memory clinics for mild forgetfulness, leading to the increased use of health care resources. Nowadays, about 25% of memory clinics patients complain of cognitive decline in absence of objective deficits (subjective cognitive decline, SCD), and they are expected to increase in the coming years. Some patients with SCD later develop cognitive impairment and dementia, often due to AD, but the majority have psychiatric conditions, physical diseases, polypharmacy, or normal brain ageing. Differentiating these potential causes is often a difficult exercise even for expert physicians. The COSCODE project, funded by Swiss National Science Foundation and led by the Geneva Memory Clinic, aims to identify possible subgroups of SCD and their associated risk of decline. This abstract is focused on the retrospective analyses of SCD patients, to develop and future validate the recruitment criteria and SCD categorization. Methods: We included 42 SCD from the Geneva Memory Clinic cohort with the following criteria:(i)Amyloid‐PET;(ii)MRI;(iii)clinical and neuropsychological evaluation;(iv)at least 1 follow‐up planned. To evaluate the representativeness of our sample we assessed the correlation between age, episodic memory and medial temporal lobe atrophy scale; Amyloid SUVr and Episodic memory. Then, a neuropsychologist and a neurologist evaluated the clinical reports in order to identify possible aetiologies of the cognitive complaint. Results: In the whole sample (age, mean±SD:71±7years; 54% female; education:16.3±4.1; MMSE:28.8±0.8; 24% A+) age is inversely correlated with episodic memory (Free‐and‐cue‐selective‐reminding‐test, p=0.003) and positively with medial temporal lobe atrophy scale (p=0.017). Amyloid SUVr correlates negatively with episodic memory performance (p<0.05). On the other hands, the clinicians found 3 different aetiologies of the SCD: Comorbidity (stroke, brain injury, cardio‐vascular risk factors, physical disability, ...), Psychopathology (depression, anxiety, personality trait); Unknown (apparently, no reason associated to the complaint). The prevalence of the 3 groups is respectively:29%, 33%, 38%. Conclusions: Our SCD sample can be considered representative of a memory clinic population, indeed it's a very heterogeneous group. The 3 groups categorization will be validated using a data driven approach and studying longitudinal trajectory of each subgroup to better understand their associated risk of decline.